Automatic procedure for evaluating the Paris Law of martensitic and austenitic stainless steels by means of thermal methods. (September 2016) - Ancona, F.; Palumbo, D.; De Finis, R.; Demelio, G.P.; Galietti, U.
Abstract: Determination of the Paris Law constants implies the knowledge of both Stress Intensity Factor (SIF) and the crack growth rate ( da / dN ). In this regard, the crack length and the SIF values can be measured using various methods suggested by literature and proposed by Standards, but most of them require an off-line measurement of the crack with consequent high testing time and cannot be applied on actual structural components. In this work, the Thermoelastic Stress Analysis (TSA) technique is used for the monitoring of fatigue crack growth during fracture mechanics tests on four stainless steels: AISI 422 and ASTMA182 grade F6NM with martensitic lattice and CF3M and CF8M with austenitic lattice. In particular, an automatic procedure based on the TSA technique was proposed for the continuous evaluation of the crack tip position and the SIF value. Advantages with respect to classical methods can be obtained in terms of reduction of: testing time, experimental set-up, data processing and data report.